2021
DOI: 10.1111/anu.13218
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish meal under different storage conditions on growth, serum biochemical indices and antioxidant capacity for juvenile grouper Epinephelus coioides

Abstract: This research aimed to assess effects of fish meal under different storage conditions on growth and antioxidant capacity for juvenile grouper within eight weeks. The healthy fish samples (initial body weight = 18.75 ± 0.05 g) were irregularly distributed to 0.5 m3 barrels with 28 fish per barrel, fed with each diet in the three replicate groups. Fish meals (FMs) were stored at 4°C (experiment 1) and room temperature (30 ± 2°C, experiment 2) for 45, 90 and 135 days, and the data of VBN, HA, AV and TBA were dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…More specifically, after 120 d, the AV, POV, p-AV, and CDV were 7.62 ± 0.14 mg/g, 23.67 ± 0.55 meq/kg, 2.33 ± 0.03, and 33.57 ± 0.89, respectively. This observed increase in the AV is also consistent with previous studies [ 24 , 25 ] and is closely related to the free fatty acid content [ 26 , 27 ]. Previously, it was reported that the oxidation of fish meat during storage causes the breakage of ester bonds, which releases a large amount of free fatty acids and increases the AV [ 28 ].…”
Section: Results and Analysissupporting
confidence: 93%
“…Free radicals scavenging is a function of the antioxidant system in the body (Liang et al, 2020a). T-AOC is the total level of various antioxidant macromolecules, antioxidant small molecules and enzymes within a system (Lin et al, 2021a). SOD GSH-Px are antioxidant enzyme systems that are closely related to free radical scavenging functions and protect important cellular macromolecules and organelles from oxidative damage (Hu et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All raw material was crushed through a 60-mesh sieve, mixed through a V-type vertical mixer (JS-14S; Zhejiang Zhengtai Electric Co., Ltd.), followed by adding with oil and water, and then pelleted (2.5 mm diameter) making use of a double screw extruder (F-75; South China University of Technology) (Song et al, 2010;Liang et al, 2020a). After the prepared experimental feed was naturally dried to about 10% moisture, it was sealed in a vacuum-packed bag and stored at -20°C until it was fed (He et al, 2021;Lin et al, 2021a).…”
Section: Diet Formulation and Preparationmentioning
confidence: 99%
“…All raw material was crushed through a 60-mesh sieve, mixed thorough a V-type vertical mixer (JS-14S; Zhejiang Zhengtai Electric Co., Ltd.), followed by adding with oil and water, and then pelleted (2.5 mm diameter) making use of a double screw extruder (F-75; South China University of Technology). After the prepared experimental feed was naturally dried to about 10% moisture, it was sealed in a vacuum-packed bag and stored at −20 • C until it was fed (He et al, 2021;Lin et al, 2021).…”
Section: Diet Formulation and Preparationmentioning
confidence: 99%